Effectiveness assertive training on discipline of learning in junior high school - Dewantari, Tri; Izzaty, Rita Eka (COUNS-EDU: The International Journal of Counseling and Education, 2018)
Discipline in learning is the obedience of students in the implementation of learning. In fact, in schools there are still students who are not in accordance with the rules of the class, do no work, come to school not on time. See things to keep in mind to improve the discipline of learning. The purpose of this study is to determine the effectiveness of training in improving student learning discipline. The method used is quasi experimental research with Non-equivalent Control Group Design. The study was conducted at SMK Trisakti Bandar Lampung, with the sample of this study is 18 students of class X Yang who have income 16-17 years. The instrument used in this study is the scale of learning discipline. Data analysis technique using Wilcoxon test. The results of this study indicate that assertive training can improve student learning discipline.